Barret's esophagus treatment - Bergalli, Luis; Rodríguez Iglesias, José Luis (Cirugía del Uruguay, 1995)
The authors discuss present medica/ and surgical treatment of Barrett's esophagus ater making a pathologica/ and historical introduction. They present therapeutical altenatives for the different forms of Barrett's esophagus according to intenational bibliograph. Barrett's esophagus is mostly considered to be the final stage of relux esophagitis, with high eposure to acid and loss of esophagical function. Complications would be linked to high alkaline exposure of the esophagical mucosa altered by duodenogastric reflux. Patients with severe dysplasia or in situ or precox carcinoma can be cured by means of resection.